Atypical bladder cancer spread – a case description - Chorąży, Marek; Bajdor, Piotr; Nasiek-Palka, Anna (Contemporary Oncology/Współczesna Onkologia, 2008)
Bladder cancer is the most frequently diagnosed kind of cancer of male patients (after lung, stomach and prostate cancers). In the case of female patients bladder cancer is diagnosed with the same frequency and it makes up 3% of all malignant neoplasms. The therapeutic procedure is determined mostly by qualifying a patient to a group of either superficial cancers or invasive (infiltrating) ones. In the case of a 72-year-old woman, who had urological treatment due to bladder cancer with non-invasive characteristics, the authors found pathological proliferation within soft tissues of the left thigh as well as ischial bone osteolytic defect. A biopsy of the tumour showed that it was a bladder cancer spread. Apart from anaemia, a high level of calcium was discovered thanks to a laboratory analysis. Palliative radiotherapy, hydration and biophosphates were used in the therapy of the patient. Normalization of results was achieved and the patient’s suffering was partly reduced